The Implementation of Congregational Prayer Activities as a Means of Character Education for Fifth-Grade Students at SD Negeri 61 Bengkulu City - Sindy Febriani; Widiya Nurhasanah Pulungan; Amisha Dwi Qomaria; Nurhadi; Ramedlon (MODELING: Jurnal Program Studi PGMI, 2023)
This study examines the implementation of congregational prayer activities as a means of character education for fifth-grade students at SD Negeri 61 Bengkulu City. The research aims to describe the implementation process, analyze the role of congregational prayer in shaping students’ religious and disciplinary character, and identify supporting and inhibiting factors. A qualitative descriptive approach was employed to obtain in-depth and contextual data related to religious activities in the school environment. Data were collected through observations, interviews, and documentation involving teachers and students. The findings indicate that congregational prayer activities are implemented in a structured and consistent manner as part of the school’s daily routine. These activities contribute significantly to the development of students’ religious awareness, discipline, responsibility, and moral behavior. Supporting factors include strong institutional commitment, active teacher involvement, adequate facilities, and structured scheduling, while inhibiting factors involve differences in students’ backgrounds, time management constraints, and limited facilities. Overall, congregational prayer activities function as an effective medium for character education in elementary school settings.